Pengaruh Social Influence, Perceived of Security dan Perceived Ease of Use terhadap Minat menjadi Nasabah Bank Digital - Nora Andira Brabo; Heni Iswati; Soeyatwoko (Syntax Literate, 2023)
This study aims to determine and analyze the influence of Social Influence, Perceived Security and Perceived Ease of Use on interest (Purchase Intention) in becoming a digital bank customer. The digitization of financial transactions has played an important role in transforming traditional payment methods into digital payment methods and has led to changes in consumer behavior around the world. Decreasing transactions through branches and transactions decrease through ATMs was inversely proportional to the rapid increase in the use of mobile banking. On the other hand, digital banks are also starting to appear to offer more effective and efficient banking services. However, to be accepted and developed, digital banks need to understand what factors (variables) really affect their success in being accepted in the market. The method of data collection was carried out using a questionnaire method with 61 questions to 113 respondents who already had bank accounts in JABODETABEK. The data analysis technique used SPSS (version 22) using a significance level of 5%. The results showed that Social Influence, Perceived Security and Perceived Ease of Use had a simultaneous and significant effect on interest (purchase intention) in becoming a digital bank customer.